Pelaksanaan Kewenangan Desa Berdasarkan Hak Asal-Usul Dan Kewenangan Lokal Berskala Desa : (Studi Di Desa Kaboro Kecamatan Lambitu, Kabupaten Bima) - Firmansyah Firmansyah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Law no.6 of 2014 concerning Villages has clarified the village's authority which was previously unclear. The village's authority in question derives from indigenous rights and local village-level authority, which is at the core of village autonomy. It began with the notion that law is considered a part of the community's life processes, not merely normative regulations. The continuation of indigenous rights in Kaboro Village, Lambitu Subdistrict, is regulated by Law No. 6 of 2014 concerning Villages, which was amended by the Minister of Home Affairs Regulation No. 44 of 2016 regarding Village Authority, followed by Bima Regent Regulation No. 2 of 2020 concerning the List of Authorities Based on Indigenous Rights and local village-level authority, which is stipulated in Kaboro Village Regulation No. 4 of 20. However, the implementation of local authority at the village level is documented in each preparation of the Village Budget (APBDesa). This is reflected in the Village Government's Work Plan, which is revised annually in accordance with the amount of the APBDesa.